Moose - Radiguès, Max de, 1982- (Conundrum International, 2015)
Joe is a shy high school student who is relentlessly bullied, and must find comfort in the natural world. Soon however, the story twists into a tale of power and fear complete with visual symbolism and beautiful cartooning. The morally ambiguous ending will keep you thinking long after you close the covers.